Conservation of Architectural and Urban Heritage Indigenous and Global Sustainable Practices - Teba, Tarek; Di Raimo, Antonino (Advances in Science, Technology & Innovation, IEREK Interdisciplinary Series for Sustainable Development, 2025)
XX, 573 p. 476 illus., 426 illus. in color.